2019
DOI: 10.1080/20013078.2019.1603048
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic characterisation of leech microglia extracellular vesicles (EVs): comparison between differential ultracentrifugation and Optiprep™ density gradient isolation

Abstract: In Mammals, microglial cells are considered as the resident immune cells in central nervous system (CNS). Many studies demonstrated that, after injury, these cells are activated and recruited at the lesion site. Leech microglia present a similar pattern of microglial activation and migration upon experimental lesion of CNS. This activation is associated with the release of a large amount of extracellular vesicles (EVs). We collected EVs released by microglia primary culture and compared two different protocols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 73 publications
4
44
0
Order By: Relevance
“…proteins in ExoCarta database. Since ExoCarta is one of the most reliable database about EVs biomolecules (Rosa-Fernandes et al, 2017) and it has been commonly used by several authors to characterize the proteomic profiles of EVs (Jeannin et al, 2018;Arab et al, 2019;Göran Ronquist, 2019), our results further confirmed the vesicular origin of identified proteins. Surprisingly, the first identified protein was serotransferrin (see Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 79%
“…proteins in ExoCarta database. Since ExoCarta is one of the most reliable database about EVs biomolecules (Rosa-Fernandes et al, 2017) and it has been commonly used by several authors to characterize the proteomic profiles of EVs (Jeannin et al, 2018;Arab et al, 2019;Göran Ronquist, 2019), our results further confirmed the vesicular origin of identified proteins. Surprisingly, the first identified protein was serotransferrin (see Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 79%
“…A 10 μL suspension of MVs was adhered to formvar/carbon-coated nickel TEM grids, negatively stained for 1 min with 3% uranyl acetate, washed with ddH 2 O and observed by TEM at an acceleration voltage of 80 kV. The size distribution and diameter of MVs were measured by NTA (NanoSight NS300, Malvern, United Kingdom), as previously described ( Arab et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Epidermal cell sheets were then treated or not for 24 h with 0.25 mM NaHS then lysed using a RLT lysis buffer (Qiagen, Hilden, Germany) for RNA-seq analyses or mechanically detached using a cell scraper for proteomics analyses. RNA-seq and proteomics analyses were performed by the Lyon-1 university genomics platform ProfileXpert and the Lille university proteomics platform PRISM (Proteomics Inflammatory Response Mass Spectrometry, INSERM U1192), respectively, as previously described [ 50 , 51 , 52 , 53 ] and detailed in the Supplementary Data.…”
Section: Methodsmentioning
confidence: 99%